TEACHER’S FEEDBACK ON STUDENTS’ WRITING ANALYTICAL EXPOSITION TEXT AT GRADE ELEVEN STUDENTS’ OF SMK NEGERI 4 MEDAN - Anggita Pratiwi; Masitowarni Siregar; Anggraini Thesisia Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
The objectives of this study were to investigate the types of teacher’s feedback in writing which given by the teachers and to find out the reason why teacher used those types of feedback on students’ writing analytical exposition text at grade eleven students’ of SMK Negeri 4 Medan. This research used descriptive qualitative method and the data were collected through documentation and interview. The framework undertaken is proposed by Ellis and the interview question was adapted from Thorsteinsen. The data was analyzed in four steps: 1). Data Collection, 2) Data Reduction, 3). Data display, 4). Conclusion and Drawing verification. The findings found that there were 5 kinds of feedback, namely direct written feedback, indirect written feedback, focus and unfocused feedback, and reformulation. The most dominant of teacher’s feedback especially on written used in students’ analytical exposition text was direct feedback. It was 56 data or 66%. Based on the analysis interview, the reason why teacher used those types of feedback on students’ writing was because it could make the students’ have more vocabularies and the students did not think more about what was the correct word. In conclusion, teacher’s feedbacks are important to make student aware of making mistake on their writing task. The finding suggested that the English teacher should give the written feedback to students’ writing task to enable them improve the writing skill. Keywords: Teacher’s Feedback, Students’ Analytical Exposition Text, Writing